Fabrication and characterization of HDPE plastic waste reinforced rubber composite - Marsi, Noraini; Huzaisham, Nur Athirah; Ithnain, Zuraidah; Main, Nor Mazlana; Mohd Rus, Anika Zafiah (Penerbit UTHM, 2020)
Plastic is one of the organic polymers that are normally made of petrochemical synthetics. The most common feature of plastic id that its manufacturing and moulding process is not difficult to carry out and the production cost, as well as its density, are also relatively low...